Fabry–Perot Microcavity Modes in Single GaP/GaNP Core/Shell Nanowires. Issue 47 (27th October 2015) - Dobrovolsky, Alexander; Stehr, Jan E.; Sukrittanon, Supanee; Kuang, Yanjin; Tu, Charles W.; Chen, Weimin M.; Buyanova, Irina A.
Abstract : Semiconductor nanowires (NWs) are attracting increasing interest as nanobuilding blocks for optoelectronics and photonics. A novel material system that is highly suitable for these applications are GaNP NWs. In this article, we show that individual GaP/GaNP core/shell nanowires (NWs) grown by molecular beam epitaxy on Si substrates can act as Fabry‐Perot (FP) microcavities. This conclusion is based on results of microphotoluminescence (μ‐PL) measurements performed on individual NWs, which reveal periodic undulations of the PL intensity that follow an expected pattern of FP cavity modes. The cavity is concluded to be formed along the NW axis with the end facets acting as reflecting mirrors. The formation of the FP modes is shown to be facilitated by an increasing index contrast with the surrounding media. Spectral dependence of the group refractive index is also determined for the studied NWs. The observation of the FP microcavity modes in the GaP/GaNP core/shell NWs can be considered as a first step toward achieving lasing in this quasidirect bandgap semiconductor in the NW geometry. Abstract : The observation of Fabry–Perot microcavity modes in single GaP/GaNP core/shell nanowires is the first step toward achieving lasing in this quasidirect bandgap semiconductor in nanowire geometry. This is an important advance to cover the yellow‐amber spectral range which is, so far, an uncovered gap for semiconductor laser diodes.